A fully reconfigurable bandpass-to-bandpass-with-embedded-stopband filter with an ultra-wide 0.09–1.41 GHz bandwidth tuning range. Issue 9 (6th June 2019) - Lan, Bo-Zhang; Qu, Yan; Guo, Chen-Jiang; Ding, Jun
Abstract: A varactor-based fully reconfigurable microstrip bandpass-to-bandpass-with-embedded-stopband filter is presented in this paper. This filter offers wide center frequency and bandwidth tuning flexibility under both bandpass mode and bandpass-with-embedded-stopband mode. The entire tuning ability is based on multiple mode resonator theory and external quality factor tuning structure for bandpass mode and the introduction of transmission zeros (TZs) for bandpass-with-embedded-stopband mode. Under the bandpass mode, the center frequency tuning range is 0.96–1.45 GHz and the bandwidth can be tuned from 0.09 to 1.41 GHz with a fixed center frequency at 1.22 GHz. Under bandpass-with-embedded-stopband mode, the center frequency and bandwidth can be tuned from 0.94 to 1.61 GHz and 0.2–0.33 GHz, respectively. Good agreements are shown between simulated and measured results.